Clear cell hidradenocarcinoma - Pohar-Marinšek, Živa (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2003)
A case of eccrine clear cell hidradenocarcinoma of sweat gland origin is presented, disclosing its clinical behavior and morphologic characteristics asevidenced by fine needle aspiration biopsy and tissue section histology. Thepatient was a 53-years old male who had a tumor on his fifth toe for 16 years. The tumor recurred 18 months after excision and metastasized widely 17 months following the amputation of the toe due to the recurrence. In spite of chemotherapy the patient died 37 months after the excision of the primary tumor. In aspirates, the tumor cells had no nuclear anaplasia and only numerous mitotic figures pointed to the malignant nature. Histologic features of malignancy were aggressive local growth, focal necrosis, angioinvasion and high mitotic index.
Keywords: Adenocarcinoma, Clear Cell; Adenokarcinom svetlocelični; Biopsija igelna; Biopsy, Needle; dermatologija; kožne bolezni; Kožne novotvorbe; kožni tumorji; Middle Age; Pathology; Prsti na nogi; Skin Neoplasms; Srednja leta; Sweat Gland Neoplasms; Toes; Znojnica, novotvorbe